Effective strategies for integrating e-learning in problem-based learning for engineering and technical education - Tasir, Zaidatun; Harun, Jamalludin; Syed Hassan, Syed Ahmad Helmi; Mohd. Yusof, Khairiyah (2005)
E-learning, through any Learning Management Systems (LMS), can be used to enhance and aid the implementation of problem-based learning (PBL). In UTM, an open-source LMS, Moodle, is being used. Through e-learning, learning can take place anywhere and anytime through the communication tools that it has. This feature provides a channel of communication among students and lecturers that is not bounded by the class time and physical presence. Therefore, e-learning has been identified as a learning system that can greatly enhance the implementation of PBL among university students. The purpose of this paper is to put forth effective strategies for utilizing e-learning in PBL for engineering and technical education. Some effective strategies that have been identified are: (1) the use of online assignment tool to deliver PBL problems to students, (2) the use of both synchronous communication tools (such as chatting) and asynchronous communications tools (such as forum and journal) for discussion and assessment, (3) lecturer-initiated communication for the PBL case on the e-learning platform, (4) frequent availability of lecturers online for facilitation, and (5) the use of online journal for reflection and assessment. These strategies enable a more efficient and effective implementation of PBL.